Chemical labeling strategies for small molecule natural product detection and isolation. Issue 9 (25th February 2021) - Hughes, Chambers C.
Abstract : Chemical labeling enhances the analysis of complex mixtures via HPLC-MS in both targeted and untargeted metabolomics workflows. Abstract : Covering: Up to 2020. It is widely accepted that small molecule natural products (NPs) evolved to carry out a particular ecological function and that these finely-tuned molecules can sometimes be appropriated for the treatment of disease in humans. Unfortunately, for the natural products chemist, NPs did not evolve to possess favorable physicochemical properties needed for HPLC-MS analysis. The process known as derivatization, whereby an NP in a complex mixture is decorated with a nonnatural moiety using a derivatizing agent (DA), arose from this sad state of affairs. Here, NPs are freed from the limitations of natural functionality and endowed, usually with some degree of chemoselectivity, with additional structural features that make HPLC-MS analysis more informative. DAs that selectively label amines, carboxylic acids, alcohols, phenols, thiols, ketones, and aldehydes, terminal alkynes, electrophiles, conjugated alkenes, and isocyanides have been developed and will be discussed here in detail. Although usually employed for targeted metabolomics, chemical labeling strategies have been effectively applied to uncharacterized NP extracts and may play an increasing role in the detection and isolation of certain classes of NPs in the future.